RelatÄ±onshÄ±p ServÄ±ce QualÄ±ty to MuslÄ±m Customer Loyalty in IslamÄ±c BankÄ±ng: SatÄ±sfactÄ±on as MedÄ±ator - sunaryo, Sunaryo (Department of Management, Faculty of Economics and Business, Brawijaya University, 2013)
The majority of the Indonesian population is Muslims. However, the market share of Islamic Banking is only 3.0% of total banks in Indonesia.This shows that the products and services offered by these Islamic banks were not optimally taken up by the Muslim community. Are service qualities and satisfaction (provided by the bank) unattractive things for Muslim? Therefore, the research was done.Â The aims of the study are to analyze the service quality that directly and indirectly affects the satisfaction of moslem customersâ€™ loyalty and the satisfaction as mediator toward Islamic bank. The study was conducted in the town of Malang with 315 respondents. The Purposive Sampling technique was used on Islamic banks in Malang. The data was analysed descriptively and inferentially by means of using SEM and the Smart-PLS. The finding from the inference analysis showed that all relations among the variables have significant influence, both directly and indirectly, and satisfaction as an intervening variable has a positive impact. Therefore, Islamic banks should give special attention to the quality of service guarantee to their customer. In addition, banks must also increase their quality service in order to make/ give more satisfaction and convenience. These findings have given new input to the theories of existing consumer behavior. The findings of this study can be used as a guide for other researchers in developing a model of consumer behavior and customer loyalty, particularly in terms of Islamic measurement model.Â